Thai Khem Kaeng: An inadequate response by the Thai State to the impact of the 2008 economic crisis - Walsh, John (Journal of Economics and Behavioral Studies, 2010)
The economic crisis erupting from inadequate regulation of reckless banking practices in 2008 was correctly met by Keynesian-style stimulus packages in governments around the world. These measures were successful when they were sufficiently large, properly focused, and implemented promptly. Where these conditions were not met, as in the case of Thailand, the results were unimpressive and the problems not dealt with properly. However, the Thai version of the second part of the stimulus package, Thai Khem Kaeng, had in fact quite a different purpose and appears to have been intended to boost the popularity of the government at the cost of making unsustainable and uncosted deficits for the future. The lack of coherence at the economic planning centre of government and its questionable methods suggest that Thailand has continued the longstanding policy of making economic decisions for non-economic reasons.